Morphophysiological adjustments to shade of jaboticaba tree saplings - Amanda Pacheco Cardoso Moura; Bruna Valéria Gil; Anelise Tessari Perboni; Fabrícia Lorrane Rodrigues Oliveira; Bruno Francisco Sant’Anna-Santos; Moeses Andrigo Danner (Revista Ceres, 2022)
ABSTRACT We aimed to verify the morphophysiological changes in jaboticaba tree (Plinia peruviana (Poir.) Govaerts) saplings under shade gradient to improve knowledge on the appropriate light environmental conditions for the saplings production and field homogeneous or intercropping cultivation of this species. The saplings were grown under full sun and artificial shade levels (30%, 50%, and 80%). Growth, photosynthetic pigments, gas exchanges, chlorophyll fluorescence, and leaf anatomy characters were evaluated. Our results showed that jaboticaba tree saplings growth was improved under full sun and 30% of shade. Under 50% and 80% shade the saplings demonstrate phenotypic plasticity, such as larger and thinner leaves. Chlorophyll fluorescence, chlorophyll content, and quantum yield of photosystem II were higher under higher shade level, but the CO2 assimilation rate was not different between light conditions. These changes are typically found in shade-tolerant plants and is related to perform photosynthesis more efficiently in highly variable light conditions. Despite that, we recommend that cultivation be carried out under full sun or up to 30% shade to maximize jaboticaba tree saplings growth in nurseries and orchards.